Pragmatics of Translation in Cross-Cultural Communication - Abduvakhabova Umida Yuspovna (International Journal on Integrated Education, 2023)
The research is devoted to the problems of pragmatic aspects in translation which serves as a bridge in dialogue of cultures, representing author and recipient of the text. This cultural sensitivity in translation implies overcoming not only linguistic but also cultural barriers, which allows us to consider translation as a type of intercultural speech activity.